Conservative Treatment of Chronic Subdural Hematoma in HIV-Associated Thrombocytopenia with Tranexamic Acid. (May 2017) - Kutty, Raja K.; Peethambaran, Anil Kumar; Sunilkumar; Anilkumar, M.
Chronic subdural hematomas (CSDHs) and its management comprise a majority work in a neurosurgical specialty. The effectiveness of surgery is beyond doubt and sometimes even lifesaving in severe cases. However, the straightforward surgery is sometimes complicated by the associated comorbidities of the patient. Comorbidities in the form of coagulopathies secondary to chronic liver diseases, drugs (warfarin, ecosprin, clopidogrel), thrombocytopenia secondary to systemic illness are always a challenge to deal with in patients with CSDH. The authors encountered a patient with thrombocytopenia secondary to systemic HIV infection who presented with CSDH. Her coagulation profile was severe enough to preclude surgery. She was managed conservatively with tranexamic acid and responded well. The authors present the challenges they faced in the course of successful management of this patient.